Artificial Intelligence Review An International Science and Engineering Journal - Liu, Derong; Robertson, David; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Artificial Intelligence Review serves as a forum for the work of researchers and application developers from Artificial Intelligence, Cognitive Science and related disciplines. The Review publishes state-of-the-art research reports and critical evaluations of applications, techniques and algorithms from these fields. Artificial Intelligence Review also presents refereed survey and tutorial articles, as well as reviews and commentary on significant developments from these disciplines. .
Keywords: Artificial intelligence; Computer science; Artificial Intelligence; Computer Science